The erotics of love and death in victorian poetry - Sıkık, Bircan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2013., 2013)
The Victorian period is well-known for its constructed understanding of "sexuality" which is one of the products of the patriarchal, imperialist and religious discourse of the age. The Victorian concept of sexuality exerts pressure on women and also on men, fixes gender roles according to a certain code of behaviour which prescribes what is ideal and what is not, and delimits Victorian women's living space accordingly. This study will explore how Victorian poetry by male authors reflects and reacts against the constructed concept of sexuality under the themes of appropriation, confinement, and evil femininity. In the light of modem and contemporary theory, this thesis focuses on how the dichotomy of love and death finds expression under the roof of eroticism in selected poems.
Keywords: English poetry -- History and criticism -- 19th century; Sex in literature.; Sexuality and literature.; Human reproduction in literature.